Kepemimpinan Pembelajaran Guru Berbasis Budaya Kearifan Lokal Dalam Menumbuhkan Profil Pelajar Pancasila Pada SMA Islam Dan Umum - Aribowo, Ahmad Nasir; Nugroho, Taufik; Wahono, Joko; Fauziah, Resvi Septian; Lestari, Silvia Oktaviana (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2023)
Research problems include student literacy and low character impact on learning outcomes, as well as the cultural value of local wisdom. The aim of the research is to describe and discover teacher learning leadership based on local wisdom culture, especially Pancasila Education, in growing the profile of Pancasila students. The research method uses qualitative. The research was carried out at public senior high school 5 and senior high school UII Yogyakarta in 2023. Research procedures include: (1) research grand tour; (2) data collection; (3) analysis; (4) results. Data collection techniques include interviews, observation, documentation. The results of the research show that teacher leadership in learning to integrate the cultural values of Yogyakarta local wisdom is able to grow the profile of Pancasila students. Local wisdom cultural values include: (1) behavior; (2) cultural products; (3) artifacts; (3) customs.